EKSPLORASI SIMBOL DAN MAKNA DALAM MANTRA PENGOBATAN MASYARAKAT DAYAK SEBERUANG - Lizawati; Uli, Indriyana (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to examine the symbolic structure and cosmological meanings embedded in the healing mantras of the Dayak Seberuang community in Gernis Jaya Village, Sepauk District, Sintang Regency. The research employs a descriptive qualitative method using the semiotic framework of Charles Sanders Peirce, focusing on the classification of signs into icons, indexes, and symbols. The data consist of eleven healing mantras recited by ritual practitioners and were analyzed through stages of sign identification, semiotic classification, meaning interpretation, and cultural contextualization. The findings reveal that the mantras function not merely as healing formulas but as a cosmological representation system that perceives illness as a disruption in the relationship between humans, spirits, and nature. Dominant symbols include the representation of spirits (antU), the concept of “tawar” as a marker of healing, the color black, sacred numbers, and medicinal plants such as muŋah and buŋkaŋ. Within Peirce’s framework, plants and herbal elements function as icons, symptoms of illness as indexes, and lexical terms such as pederak, sawan, and datai dara/bujaŋ as culturally constructed symbols. The study contributes to the development of semiotic analysis based on the icon–index–symbol classification in the study of Dayak oral literature and integrates textual and anthropological approaches in understanding mantras as cultural sign systems grounded in local wisdom.